2022
DOI: 10.1108/ijse-05-2022-0339
|View full text |Cite
|
Sign up to set email alerts
|

Impact of financial inclusion on economic growth: review of existing literature and directions for future research

Abstract: PurposeThe impact of financial inclusion on economic growth is a topic that is generating widespread interest among researchers and practitioners. In this paper, the authors review the existing literature to highlight the state of research in the literature and identify new opportunities for innovative research.Design/methodology/approachThe authors used a thematic literature review methodology which involves dividing the review along relevant themes.FindingsThe authors find that significant research on the to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 44 publications
(25 citation statements)
references
References 47 publications
0
24
0
1
Order By: Relevance
“…(2000), Poshakwale and Qian (2011), Ayadi et al . (2015), Ozili et al . (2022b), Haggard and Tiede (2011) and Haidar (2012).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…(2000), Poshakwale and Qian (2011), Ayadi et al . (2015), Ozili et al . (2022b), Haggard and Tiede (2011) and Haidar (2012).…”
Section: Methodsmentioning
confidence: 99%
“…In total, eight variables were used in the empirical analyses. The eight variables used in the analyses have been used in previous studies such as Owusu (2012), Matei (2020), Ozili et al (2022a), Ruiz (2018), Mian et al (2017), Beck et al (2000), Poshakwale and Qian (2011), Ayadi et al (2015), Ozili et al (2022b), Haggard and Tiede (2011) and Haidar (2012). The dependent variables are the logarithm of the GDP per capita (LogCGDP) variable and the GDP growth rate (RGDP) variable.…”
Section: Ajems 144mentioning
confidence: 99%
See 1 more Smart Citation
“…Existing studies show that financial inclusion is related to economic growth. Ozili et al (2022a) review the existing literature on the impact of financial inclusion on economic growth and found that significant research on the topic emerged in the post-2016 years. It was also found that the most common channel through which financial inclusion affects economic growth is through greater access to financial products and services offered by financial institutions which increases financial intermediation and translates to positive economic growth.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Financial inclusion improves access to finance which increases consumption, production and investment, thereby leading to increase in economic output and higher economic growth (Erlando et al , 2020). Few studies have empirically examined the effect of financial inclusion on economic growth (Sethi and Acharya, 2018; Erlando et al , 2020; Ozili et al , 2022a). But there is little evidence on this relationship in religious settings.…”
Section: Introductionmentioning
confidence: 99%